Short-term Alteration of Renal Function and Electrolytes after Percutaneous Nephrolithotomy - Mukherjee, Subhabrata; Sinha, Rajan Kumar; Jindal, Tarun; Sharma, Pramod Kumar; Mandal, Soumendra Nath; Karmakar, Dilip (Urology Journal, 2019)
Purpose: To analyse the changes in renal function and serum electrolytes in the early post-operative period of percutaneous nephrolithotomy (PCNL). Materials and Methods: A total of 110 patients with normal renal function, who underwent PCNL in our institute were evaluated prospectively. Haemoglobin percentage, packed cell volume, blood urea nitrogen, serum creatinine and serum electrolytes, namely sodium, potassium, chloride and ionized calcium were measured on the day before surgery and after 72 hours of the procedure. Renal function was assessed by Cockcroft-Gault formula and estimated glomerular filtration rate was calculated by modification of diet in renal disease formula. Results: Serum creatinine increased significantly from a mean value of 0.89 ± 0.199 mg/dL to 0.96 ± 0.252 mg/dL (P = 0.0002) and both creatinine clearance and estimated glomerular filtration rate experienced a significant fall - from a median value (interquartile ranges) of 82.99 (72.37 to 96.88) mL/min to 75.38 (63.89 to 94.05) mL/min in case of creatinine clearance (P = 0.0004) and from a mean value of 95.18 ± 19.87 mL/min/1.73 m2 to 89.30 ± 23.14 mL/min/1.73 m2 in case of estimated glomerular filtration rate (P = 0.003). Furthermore, there were significant drops in both haemoglobin percentage and packed cell volume. There were no significant alterations in serum electrolytes - sodium and potassium (mmol/L) [Median (IQR)] changed from a pre-operative figure of 137.5 (134.0 to 140.0) and 3.85 (3.60 to 4.10) to a post-operative value of 138 (135.0 to 140.0) and 3.85 (3.50 to 4.10) respectively. Conclusion: Even though there is no significant variation in serum electrolytes, PCNL causes significant reduction in renal function in the early post-operative period.